Maddigan, Bernadette. Interview about fairy lore. - Tennier-Stuart, Emma (2014)
Emma Tennier-Stuart interviewing Bernadette Maddigan in her home about fairy lore in Witless Bay, Newfoundland. Recorded by Sharna Brzycki 0:00 – Introduction; 0:25 – Story about a man who heard fairies talking while he camped; 2:55 – BM has never seen any fairies, and wouldn’t want to; 3:35 – No special names for the fairies; mother told her the fairies were fallen angels; “There are things put on earth to frighten you”; 4:15 – Fairies are all bad, because they take people; 4:30 – Brother has a story about a man taken by the fairies on Belle Isle; fairies left a fairy in his place; the fairy was a skilled mechanic; 5:05 – Nun told her a story about a baby taken and replaced with a baby fairy; no special name for a fairy left in a human’s place; 6:05 – Story about a man taken by the fairies and found under a house; he spoke with slurred speech for the rest of his life; 6:45 – Interruption as Ralph Carey enters house; 6:50 – Continuing story of the man found under a house; 7:15 – BM does not know how to describe fairies; 7:30 – Anybody can be taken by the fairies; 7:50 – The fairies are fallen angels; 8:00 – She believes in fairies; 8:15 – She could walk alone at night and not see any fairies; 8:30 – Story of a little girl who was taken by the fairies in the daytime, and was found miles away; she was never the same and spent the rest of her life in psychiatric institutions; 9:30 – Nuns and priests only sometimes talked about fairies; repeat of story about the baby replaced by a fairy; 10:05 – You just know when a fairy is there in place of a person; 10:30 – There are no good fairies; 10:50 – Tokens; BM saw a token of her cat two days before it died; 11:25 – Never heard of anyone coming back gifted after being taken by the fairies; they are not the same person; 11:50 – Fairies are frightening; “All fairies shouldn’t be on earth”; 12:05 – No stories of fairies and animals interacting; animals can have tokens; BM once saw ghost cow; 14:15 – BM's mother warned her about fairies, and was always afraid; 15:10 – It is ...